TINGKAT PENDIDIKAN ORANG TUA: Antar Motivasi Belajar dan Kebiasaan Bermain Game Online - Fidya Hariani; Wiwin Arbaini; Dini Palupi Putri (Universitas Islam Sultan Agung, 2020)
This study aimed to find out a depiction of educational patterns of parents whose educational background was elementary education in guiding and motivating their children often playing online games. This study applied a qualitative approach. Data were collected through observations and interviews. After the data had been collected, they were then analyzed using the theory of Miles et al, namely data reduction, data presentation, and conclusion drawing. The study concluded as follows: first, parents’ level of education had an implication on the lack of parental motivation in Tanjung Alam Village. It happened because there were still many parents who did not really understand the educational process. Second, the habit of playing games by teenagers in Tanjung Alam Village became the implication of the lack of parents’ knowledge as regards technological development and the negative impact of playing online games so that parents did not realize that this habit had an impact on the lack of learning activities at home.Keywords: Parental education, learning motivation, online games